5, 5′‐Methylenedisalicylic Acid (MDSA) Modulates SarA/MgrA Phosphorylation by Targeting Ser/Thr Phosphatase Stp1. Issue 7 (24th March 2015) - Zheng, Weihao; Liang, Yujie; Zhao, Hui; Zhang, Jianing; Li, Zigang
Abstract SarA (staphylococcal accessory protein A), MgrA (MarR family of global transcriptional regulator A), and SarZ (a paralogue of SarA) play critical roles in modulating the virulence, drug resistance and autolysis of Staphylococcus aureus. Recently, eukaryotic‐like Ser/Thr kinase/phosphatases (Stk1/Stp1) were found to modulate phosphorylation of these transcriptional regulators as well as staphylococcal virulence. Importantly, an stp1‐deficient strain showed significant virulence reduction in mice, indicative of Stp1 as a potential drug target. Here, we report that MDSA, an inhibitor of MgrA, enhances phosphorylation of SarA/MgrA by inhibiting Stp1 in S. aureus. MDSA is a more‐potent inhibitor (IC50=9.68±0.52 μM) of Stp1 than commonly used phosphatase inhibitors. We anticipate that MDSA could be a lead compound to develop new approaches for reducing staph virulence by targeting Stp1.